RELEVANSI TEORI SOSIAL KOGNITIF ALBERT BANDURA TERHADAP ILMU PENDIDIKAN ISLAM - Iqbal, Muhammad; Nadilla (Program Studi Manajemen Pendidikan Islam, 2024)
The relevance of Albert Bandura's Social Cognitive Theory to Islamic Education, namely the theory that explains modeling/modeling discovered by Albert Bandura with the theory contained in Islam, namely Uswatun Hasanah, these two theories explain the formation of a person's personality based on modeling or imitation carried out by other people. , a person imitates the behavior of another person whose behavior becomes his own. Modeling is social learning that a person obtains from their environment and cognition. For example: students use their teachers as role models both in terms of cognitive and behavioral aspects. Students tend to imitate and model whatever they observe from their teachers. Therefore, teachers should be examples and role models for their students, teachers must have a good personality as reflected in teacher competence, namely teachers must have a person with noble character. The noble morals that a teacher must have are reflected in the mandatory characteristics of the Prophet, namely the characteristics of Siddiq, Amanah, Fathanah, and Tabligh. These are the qualities that teachers must have in order to create knowledge and good morals for their students. Modeling is a theory that can create quality students and develop adequate human resources.